2008
DOI: 10.1186/1752-0509-2-60
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen dependence of metabolic fluxes and energy generation of Saccharomyces cerevisiae CEN.PK113-1A

Abstract: Background: The yeast Saccharomyces cerevisiae is able to adjust to external oxygen availability by utilizing both respirative and fermentative metabolic modes. Adjusting the metabolic mode involves alteration of the intracellular metabolic fluxes that are determined by the cell's multilevel regulatory network. Oxygen is a major determinant of the physiology of S. cerevisiae but understanding of the oxygen dependence of intracellular flux distributions is still scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
118
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 79 publications
13
118
1
Order By: Relevance
“…Up till now, metabolic profiling and flux analysis have been established for analyzing intermediate metabolites in ethanol fermentation with Saccharomyces cerevisiae under low and normal concentration substrate conditions (Jouhten et al, 2008;Nissen et al, 1997;Varela et al, 2004), but how metabolic flux distribution is affected under VHC conditions has been rarely exploited. Devantier et al (2005) performed metabolic profiling analysis for batch VHC fermentation, but so far no related study has been reported for continuous VHC ethanol fermentation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, metabolic profiling and flux analysis have been established for analyzing intermediate metabolites in ethanol fermentation with Saccharomyces cerevisiae under low and normal concentration substrate conditions (Jouhten et al, 2008;Nissen et al, 1997;Varela et al, 2004), but how metabolic flux distribution is affected under VHC conditions has been rarely exploited. Devantier et al (2005) performed metabolic profiling analysis for batch VHC fermentation, but so far no related study has been reported for continuous VHC ethanol fermentation systems.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of oxygen in the culture medium can shift the central yeast metabolism from fermentative to respiratory (30,32,50,60). However, Saccharomyces cerevisiae shows a fully respiratory metabolism only at low growth rates with low sugar concentrations (20).…”
mentioning
confidence: 99%
“…In S. cerevisiae, ethanol biosynthesis reactions contribute mainly to the oxidization of NADH produced through glycolysis to maintain the intracellular balance of NADH and NAD + . 52) Moreover, when the ethanol biosynthesis pathways are disrupted, glycerol biosynthesis is induced to oxidize NADH produced through glycolysis. 53,54) Hence, in our experiments, glycerol production was increased in ADH1-5-disrupted strains S149 and S149sdh12.…”
Section: Resultsmentioning
confidence: 99%